2019
DOI: 10.1007/s42729-019-00073-4
|View full text |Cite
|
Sign up to set email alerts
|

Seed Pre-treatment with Polyhydroxy Fullerene Nanoparticles Confer Salt Tolerance in Wheat Through Upregulation of H2O2 Neutralizing Enzymes and Phosphorus Uptake

Abstract: Polyhydroxy fullerenes nanoparticles (PHF) are regarded as free radical sponges. Can they mitigate oxidative stress and induce tolerance in plants exposed to salinity? The influence of PHF seed pre-treatment on growth and biochemical attributes of NaClstressed wheat is studied. Wheat seeds (cv. Ujala) were pre-treated with control, hydro-priming, 10, 40, 80, and 120 nM PHF doses for 10 h and grown in sand-filled pots under control (0 mM NaCl) and salinity (150 mM NaCl) provided through nutrient solution. Salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 62 publications
(65 reference statements)
2
29
0
Order By: Relevance
“…Also, the seedlings exhibited better osmotic ion adjustments (particularly K ? and P ions) and less content of MDA and H 2 O 2 (Shafiq et al 2019). On the basis of these short-term effects of PHF as seed priming agent, we further hypothesized that its foliar spray might also promote salt tolerance in wheat.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, the seedlings exhibited better osmotic ion adjustments (particularly K ? and P ions) and less content of MDA and H 2 O 2 (Shafiq et al 2019). On the basis of these short-term effects of PHF as seed priming agent, we further hypothesized that its foliar spray might also promote salt tolerance in wheat.…”
Section: Introductionmentioning
confidence: 94%
“…In our previous study, seed pre-treatment with PHF at nano-molar concentrations promoted salt tolerance in 30-day old wheat seedlings through improvements in chlorophyll contents, free amino acids, total sugars and enhancing the activities of H 2 O 2 scavenging enzymes viz. CAT, POD and APX (Shafiq et al 2019). Also, the seedlings exhibited better osmotic ion adjustments (particularly K ?…”
Section: Introductionmentioning
confidence: 94%
“…3a-c). The salt-induced reduction in chlorophyll pigments has been reported earlier in a number of crops including wheat (Acosta-Motos et al 2017;Shafiq et al 2019). The extent of saltinduced reduction in chlorophyll a and b contents depends on the salt tolerance potential of plants (Hamada and El-Enany 1994).…”
Section: Discussionmentioning
confidence: 68%
“…It is now well evident that high concentrations of soluble salts cause both osmotic stress and ionic stress, which can effectively damage the photosynthetic apparatus and hamper a myriad of physio-biochemical processes (Acosta-Motos et al 2017;Shafiq et al 2019). For example, Ashraf and Harris (2005) reported that salinity-induced stomatal closure and reduced rate of leaf expansions lead to consequently restrict plant growth and yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation